2012
DOI: 10.1088/1751-8113/45/9/095203
|View full text |Cite
|
Sign up to set email alerts
|

A finite genus solution of the Hirota equation via integrable symplectic maps

Abstract: Two integrable symplectic maps are constructed through nonlinearization of the discrete linear spectral problems in the Lax pair of the Hirota equation, i.e. the lattice sine-Gordon equation. As an application, these maps are used to calculate the finite genus solutions of the Hirota equation and the closely related lattice potential MKdV equation, i.e. the special H3 model in the Adler–Bobenko–Suris list.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…In this paper, we exhibited a new version of the algebro-geometric approach to deal with the partial difference equations of KdV-type, which is different from the existing results in the literatures. 16,41,42 We have presented examples of integrable symplectic maps and finite genus solutions for lattice KdV-type equations. In the lpKdV and lSKdV cases, there are two discrete potentials, and we need to impose constraints between them to construct the algebro-geometric solutions using the technique of nonlinearization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we exhibited a new version of the algebro-geometric approach to deal with the partial difference equations of KdV-type, which is different from the existing results in the literatures. 16,41,42 We have presented examples of integrable symplectic maps and finite genus solutions for lattice KdV-type equations. In the lpKdV and lSKdV cases, there are two discrete potentials, and we need to impose constraints between them to construct the algebro-geometric solutions using the technique of nonlinearization.…”
Section: Resultsmentioning
confidence: 99%
“…41, integrable symplectic maps and novel theta function solutions for Equation () were constructed through integrable Hamiltonian systems associated with the continuous sG equation. In contract, in this paper, we start from the Kaup‐Newell spectral problem 45 xχ=Vfalse(λ;v,wfalse)χ=λ2/2λvλwλ2/2χ,and the associated discrete spectral problem χ=(λ2β2)1/2D(β)false(λ;afalse)χ,D(β)false(λ;afalse)=λaββλa1.In this example, we actually have a different type of situation from the one of the previous examples 16,41,42 since the relation between the discrete potential a and the continuous potentials v,w is implicit. However, based on the Lax structure of the Kaup‐Newell equation, (), the system can still be nonlinearized, in the sense mentioned above, as an integrable symplectic map.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding elliptic information to integrable systems, either to equations or to solutions, is an interesting topic, which brings the study of the integrable systems into a larger area and more insight [26][27][28][29][30][31][32][33]. In this paper, we have shown that the Cauchy matrix approach works for the study of some elliptic integrable systems, i.e.…”
Section: Discussionmentioning
confidence: 99%